185k views
5 votes
3+k(6+ h); use h = 5, and k = 4

2 Answers

5 votes

Answer:

hello.

Explanation:


3 + k(6 + h) \\ 3 + 4(6 + 5) \\ 3 + 4(11) \\ 3 + 44 = 47

it's easy just try.

User Deadly
by
5.4k points
4 votes

Answer:

47

Explanation:

Substituting in the given value for h and k, the expression becomes

3+4*(6+5)

Step 1: Parenthesis

3+4*(6+5) = 3+4*(11)

Step 2: Multiplication

3+4*11 = 3+44

Step 3: Addition

3+44 = 47

User Spume
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.